Parallel in vitro ion channel and in vivo zebrafish assaying of elapid snake venoms following chromatographic separation of toxin components - Arif Arrahman; Haifeng Xu; Muzaffar A. Khan; Tijmen S. Bos; Julien Slagboom; Guus C. van der Velden; Ulrike Nehrdich; Nicholas R. Casewell; Michael K. Richardson; Christian Tudorache; Fernanda C. Cardoso; Jeroen Kool (SLAS Discovery)
Snake venoms are complex bioactive mixtures designed to paralyse, kill, or digest prey. These venoms are of pharmacological interest due to their ability to modulate molecular targets such as ion channels and receptors with high specificity and potency. Traditional studies often focus on in vitro molecular analysis or in vivo behavioural effects, limiting comprehensive understanding. Here, we present a high-throughput screening platform that combines in vitro ion channel assays with in vivo zebrafish larval bioassays using nanofractionation analytics. This method integrates post-column calcium flux assays, zebrafish paralytic bioassays, toxin mass spectrometry, and proteomics to link bioactivity with toxin identification. Using elapid snake venoms (genus Dendroaspis, Naja, and Hemachatus) as a proof of concept, we identified several toxins modulating ion channels with paralytic effects on zebrafish larvae. Our approach enables parallel acquisition of in vitro and in vivo data, offering a robust guide for identifying and characterising ion channel modulators with defined molecular targets.